The Implementation of the Safekeeping Agreement (Consignment) In Supermarket - Nursasongko, Fitriaji Wira (Law Development Journal, 2021)
Along with the times, the economy in the current era is diverse and growing very rapidly, especially in the business world. Many business activities require cooperation from other business actors with the aim of developing business potential, businesses between these business actors are usually based on trust between parties as the main basis for building businesses that can mutually benefit each other. One of the cooperation agreements is the safekeeping of goods (consignment). In practice, the goods custody agreement (consignment) requires good cooperation and the goods sold must be of good quality in accordance with the provisions contained in the Kedungmundu Style Supermarket. This study aims to find out the procedures and implementation of the consignment agreement at the Gaya Kedungmundu Supermarket, Semarang, to find out the problems or obstacles that exist in the implementation of the consignment agreement at the Kedungmundu Supermarket Semarang in the event of a default between the two parties. The method used in this study is a sociological juridical approach, which is carried out by using an approach using the assistance of other social sciences, through this approach it means that in the study of the data it is not only guided by juridical aspects. But by looking at the reality in practice. The specification of the research conducted is descriptive analysis. This research analyzes and presents facts systematically so that it can be easier to understand and conclude. Based on this research, it can be concluded that the procedure for implementing a consignment agreement at the Gaya Kedungmundu Supermarket, Semarang, starting from filling out the stages to be able to cooperate in a consignment relationship, requires an agreement and there is no coercion from other parties according to Article 1320 of the Civil Code. in the implementation of the goods safekeeping agreement (consignment) which includes internal and external obstacles. Efforts to complete the implementation of the goods safekeeping agreement (consignment) include litigation and non-litigation, for example through legal channels and deliberation or negotiation.